+0  
 
0
31
1
avatar

x²-4x+13=0

 
 Nov 22, 2020
edited by Guest  Nov 22, 2020

Best Answer 

 #1
avatar+10581 
+2

Hello Guest!

 

\(x²-4x+13=0 \)

        p          q

\(\color{blue}x=-\frac{p}{2}\pm \sqrt{(\frac{p}{2})^2-q}\\ x=2\pm\sqrt{2^2-13}\\ x=2\pm\sqrt{9\cdot(-1)}\\ x=2\pm3 \sqrt{-1}\\ x=2\pm3i\)

\(x_1=2+3i\\ x_2=2-3i\)

laugh  !

 
 Nov 22, 2020
 #1
avatar+10581 
+2
Best Answer

Hello Guest!

 

\(x²-4x+13=0 \)

        p          q

\(\color{blue}x=-\frac{p}{2}\pm \sqrt{(\frac{p}{2})^2-q}\\ x=2\pm\sqrt{2^2-13}\\ x=2\pm\sqrt{9\cdot(-1)}\\ x=2\pm3 \sqrt{-1}\\ x=2\pm3i\)

\(x_1=2+3i\\ x_2=2-3i\)

laugh  !

 
asinus Nov 22, 2020

36 Online Users

avatar
avatar
avatar
avatar